Submental intubation in oral and maxillofacial surgery: a systematic review 1986–2018. Issue 1 (January 2020) - Goh, E.Z.; Loh, N.H.W.; Loh, J.S.P.
Abstract: Submental intubation is a low-risk alternative to tracheostomy when nasotracheal or orotracheal intubation is not appropriate. To improve the selection of patients and clinical outcomes we have explored published papers on submental intubation in oral and maxillofacial surgery, and included a proposal for a decision pathway. Systematic searches of PubMed, Scopus, and Cochrane databases for papers published between 1986 and 2018 yielded 116 eligible articles (one randomised controlled trial, 61 case series, 40 case reports, six surgical techniques, and eight letters) that included 2 229 patients. Measured outcomes were the indications, techniques, devices used, time taken to complete the procedure, and complications. Indications were trauma (81%), orthognathic surgery (15%), disease (2%), and cosmetic surgery (1%). Technical preferences were for a one-tube (84%) over a two-tube technique (6%), and a paramedian (52%) over a median incision (33%). The preferred device was a reinforced endotracheal tube (85%). The mean (range) intubation time was 10 (2–37) minutes. The complication rate was 7% (n = 152), the most common being superficial skin infection (n = 54), hypertrophic scarring (n = 18), and damage to the tube apparatus (n = 15). Submental intubation has minimal complications, takes a short time to do, and it is a useful alternative to tracheostomy in some oral and maxillofacial operations. More robust evidence regarding the selection of patients, modifications to the technique, and a comparison of risk with that of tracheostomy, are needed for further evaluation of its feasibility.